The Principal's Role in Implementing Religious Moderation Values in Junior High School of Tanjung Beringin District - Alfisyah, Nandalifia; Harfiani, Rizka; Setiawan, Hasrian Rudi (FIKROTUNA: Jurnal Pendidikan dan Manajemen Islam, 2024)
This study examines the role of school principals in implementing religious moderation in three junior high schools (SMP) in Tanjung Beringin Sub-district, Serdang Bedagai Regency, focusing on leadership practices that support the creation of a harmonious and inclusive educational environment. Using a qualitative approach with a phenomenological design, this study aims to explore an in-depth understanding of the educational dynamics that occur in the context of religious diversity at the junior high school level. Data were collected through observation, in-depth interviews with principals, teachers and students, and analysis of relevant documents. Data analysis was conducted interactively and continuously through three stages: data reduction, data presentation, and conclusion drawing. The results showed that principals at SMP Negeri 1 Tanjung Beringin, SMP Negeri 4 Tanjung Beringin, and SMP Swasta Berdikari play a significant role in promoting religious moderation through inclusive policies and practices. As managers, principals implement principles such as collective prayers, 3S (Smile, Greet, and Salute) activities, and participation in religious activities, which form a harmonious atmosphere in the school. As leaders, they provide direction through regular meetings to reinforce the values of tolerance and mutual respect. As supervisors, principals ensure that there is no discrimination or disharmony in the school environment, and as administrators, they work closely with the community to create a conducive environment. Overall, the role of school principals is crucial in building inclusive and tolerant schools and supporting the implementation of religious moderation among students.